(untitled) (Research Nepal Journal of Development Studies, 2018)
Major problem of Nepalese economic transformation is lack of educational willingness of development practiceners. This study has been conducted to analyze the theories of economic transformation, to check the initiation of economic transformation in Nepal, to analyze the rural electrification and benefit sharing. It is based on secondary information of library method. It is a review of related documents of economic transformation, benefit sharing and hydropower projects of Nepal. The study shows that theories on Economic Transformation are necessary to revise; Economic Transformation in Nepal is yet to start; Rural Electrification is not economic transformation from hydropower projects in Nepal; Benefit sharing in Nepal is not satisfactory. Research Nepal Journal of Development Studies Vol.1(1) 2018 94-99